Kemampuan Menyusun Soal Berbasis HOTS Guru Bahasa Jawa SMK Negeri Se-Kabupaten Kendal - Setyaningrum, Triska Ayudya; Alfiah, Alfiah; Sulanjari, Bambang (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
This study aims to describe the results of the ability of Javanese language teachers in compiling Higher Order Thinking Skills (HOTS) -based questions in State Vocational High Schools in Kendal Regency. This research was conducted in four State Vocational High Schools (SMK) in Kendal Regency using descriptive qualitative research methods. The data in this study were questions. The final test of even semester in class X was obtained through documentation techniques, then the data was examined and the questions were coded. Furthermore, the data was studied using descriptive analysis techniques. From the analysis, it was found that the ability of Javanese language teachers in compiling HOTS-based questions was still dominated by LOTS elements. This is evident from the total number of questions found that the percentage level of cognitive level Cl is 0%. C2 cognitive level is 59.42% or it can be said that more than half of the maximum result. This percentage is obtained from 104 questions. In addition, there is a C3 cognitive level of 3.42% or consisting of six questions. The questions included in the C4 cognitive level were 37.14% or as many as 65 items. In the level of questions at the C5 cognitive level of 0% or not found the corresponding questions. The highest cognitive level of high-order thinking skills is C6 at 0% or there are no questions that use this cognitive level. It can be concluded that the ability to compose questions based on HOTS for Javanese language teachers of SMK in Kendal Regency is 37.14%.